A construção da legitimidade do empreendedor institucional na revitalização dos polos varejistas de rua - Silva, André Luiz Barbosa da (2017)
High street retailers play an important role in the vitality of cities. However, due to market changes and the rapid expansion of direct competitors, their survival has been threatened. One of the strategies to reverse this process is the project of revitalization that aims to raise the attractiveness of the high street retailers. In Brazil, unlike the international context, there is no institutionalized model with specific legislation that allows a cohesive articulation and mobilization for the revitalization process between the public and private sectors. In some Brazilian states, few initiatives have been developed due to the concerns of some retailers in the high street retailers or of organizations outside the field. These retail leaders became institutional entrepreneurs (IE) because they were actors who made strong efforts to modify and structure the organizational field for the street retailers. However, to act as IE these retailers had to build their legitimacy among their peers and later with external institutions. But this process of building legitimacy requires a lot of effort from the IE, otherwise it will not be able to propose the deinstitutionalization of the existing structures in search for new organizational forms. Throughout this context, the main objective of this research is to describe how IE build their legitimacy in fields not yet institutionalized, as is the case of the high street retailers in Brazil, and how these 'pre-emergent' fields influence this process. With the proposal to clarify these issues, this research was based on a qualitative approach and applied a multiple case study design. A series of semi-structured interviews were conducted with retailers that acted as institutional entrepreneurs in the revitalization project, totaling eight high street retailers in Brazil. In addition to the interviews, observations, collection, analysis of documents made available by the entrepreneurs and research of secondary data on the web were carried out to add depth to the case studies. Our results showed the difficulties of retail entrepreneurs to raise the degree of maturity of the high street retailers the presentation of a structured project, with collective benefits and with the purpose of increasing local attractiveness, was not sufficient to guarantee the construction of the legitimacy of the retail institutional entrepreneur in its integrity. In addition, our analysis s indicated a strong influence of the precarious degree of institutionalization of the high street retailers in the construction of the legitimacy of the retail institutional entrepreneur (RIE). The high street retailers were positioned in the organizational field in such a poorly structured stage that we have come to call it the “pre-emergent” field. Thus, our research generates contribution to better describe how institutional entrepreneurs retailers sought to build their legitimacy among their peers and towards the other social actors outside the high street retailers. We also contribute to generating managerial recommendations for the high street retailers itself, as well as for public policies to effectively support and even stimulate the high street retailers’ revitalization process and thus avoid the phenomena of degradation in the central areas of cities